Sosialisasi Manajemen Waktu dan Motivasi Belajar Dalam Meningkatkan Prestasi Belajar Remaja - Reza, Bobby; Prasetyo, Sisman; Nugroho, Prasetyo Adi; Lukiyana, Lukiyana; Putra, Bagas Kautsar Azizal; Salini, S.Sarwita; Rafi, Muhammad; Kaylasalma, Nazla (Universitas 17 Agustus 1945 Jakarta, 2024)
This program is conducted to provide education on time management and efforts to improve and maintain learning motivation for adolescents at the junior high school level. This program is expected to have a positive impact on participants in terms of time management and increasing motivation, so that learning achievement can be improved. Education through socialization was conducted at SMP Negeri 2 Muaragembong, Jayasakti Village, Bekasi. The methods used were socialization and Question & Answer. The information analyzed showed that a good understanding of time management and a high level of learning motivation contributed to improving adolescent achievement. The results of this activity provide recommendations for adolescents and education partners to improve their understanding and practice of time management and learning motivation in order to achieve improved learning achievement in Jayasakti Village.